Effects of the HDI on CO2 Emissions in Latin America and the Caribbean - Villegas Pocaterra, Esmeralda; Molero Oliva, Leobaldo Enrique; Rodríguez López, Virginia Elizabeth; Andino Chancay, Tanya Shyrna (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The purpose of this research is to assess the effect of the Human Development Index (HDI) on carbon dioxide emissions per capita with data from 19 countries in Latin America and the Caribbean for the period 1990-2019 with annual frequency. Regarding the level of human development, the indices of the income, health and education dimensions were estimated. A quantile regression was used to evaluate the effect of the HDI regressor on the different quantiles of the distribution of emissions per capita. According to the results, the effect is greater in the upper deciles of the distribution of emissions, therefore, if specific policies are not assumed in the environmental dimension, the achievement of higher levels of human development, indicated by a higher HDI, would have pernicious consequences on emissions, making development not go hand in hand with environmental sustainability.